Differentiation of the energetic parameters between male and female elite pole vaulters - Warburton, T.; Lyttle, A.; James, R.; Alderson, J. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
This study aimed to examine whether differences were evident in the average energetic waveforms and energy summary results between four male and four female elite pole vaulters. Full body DXA scans and 3D body surface scans were conducted for each of the athletes to allow subject specific body segment inertial parameters to be calculated. A total of 67 vaults were recorded across the 8 vaulters, with a 3D kinematic analysis being performed on each vault. Translational and rotational kinetic energy; and gravitational potential energy were derived from this analysis and used to calculate total vaulter energy. Average summary energy values and energetic waveforms were compared between the male and female vaulters. Significant differences were found in some of the initial energy values as well as variables related to the pole extension phase.